Review of Active Synchronization for Renewable Powered Microgrid - Aisyah Mohd Yusof, Nur; Ali, Zaipatimah (International Journal of Engineering and Technology, 2019)
Microgrid can operate in dual mode; grid-connected and islanded mode. In order to seamless transfer from islanded microgrid to grid connected mode, it is necessary to voltage, frequency and phase of microgrid to synchronize with main grid to prevent severe consequence. However, microgrid has to be controlled in a coordinated way to achieve a synchronization. This paper present a review on the existing active synchronization approach with their control strategies. There are three approach for grid-connected synchronization; active synchronization, passive synchronization and open transition transfer. However, only active synchronization approach provides the reliable reconnection for microgrid. Active synchronization approach associates with control structures and control strategies. There are three control structures of microgrid under active synchronization; centralized, decentralized and distributed and three control strategies available in the literature which are phase locked loop (PLL), droop control, and frequency locked loop (FLL). The most applicable control strategy for active synchronization is phase locked loop because of its simplicity, robustness, and effectiveness in various main grid condition. Furthermore, between three control structures of active synchronization, decentralized control is becoming more favorable by the researches based on its advantages over the other structures. Â Â